Muslim discourse on international human rights: the problem of harmonization - Haneef, Sayed Sikandar Shah (2013)
The concept of human rights as embodied in the Universal Declaration of Human Rights undisputedly is a western construct. But since Muslim states at the official plane have committed themselves to its tenets by being signatory to it as members of the United Nations, their afterthought has triggered a debate among the academia about its harmonization with the Islamic notion of human rights. Some reject it in its entirety, others advocate its adoption even at the expense of some Islamic core values and yet another body of opinion sees it in total conformity with Islam. This paper argues that all the above perspectives in spite of their merits miss one important point, namely addressing the issue in the context of Muslim- nation- states interacting with the comity of nations with their own specific value systems. Accordingly, the harmonization in line with the legitimate Islamic methodology is the real alternative which this presentation endeavors to articulate.